Design of a metal-based deformable mirror for orthogonal beam deflection and highly dynamic beam oscillation - Boettner, Paul; Peschel, Thomas; Brady, Aoife; Heinig, Daniel; Goy, Matthias; Eberhardt, Ramona; Nolte, Stefan (Optics Express, 2022)
We report on an opto-mechanical metal mirror design for highly dynamic, diffraction-limited focus shifting. Here, the mechanical geometry of the membrane is of crucial interest as it must provide sufficient optical performance to allow for diffraction limited focussing and have a high mechanical eigenfrequency to provide dynamic motions. The approach is the analytical consideration of the plate theory and provides the basis for a parameterized finite element model. By means of an finite element analysis (FEA), essential steps for the optimization of the mirror design with respect to a wide range of optical power and a high operating frequency are shown. To verify the results of the FE analysis, the deformed surface is decomposed into Zernike coefficients. An analysis of the point spread function is performed to evaluate the optical performance. For dynamic evaluation a modal and a harmonic vibration analysis are conducted. The opto-mechanical design allows a biconical deformation of the mirror surface, enabling the generation of a diffraction-limited spot diameter in the adjustment range of ±1.2 dpt. The surface shape error in this range is 53 nm. The dynamic analysis shows the first excited eigenfrequency at 21.6 kHz and a diffraction-limited operation frequency at 9.5 kHz. This paper provides an alternative design approach for highly dynamic beam oscillation in the Z direction, forming a complement to highly dynamic X-Y scanning systems.
CRIS-Team Scopus Importer:2023-04-20